APPLICATION-BASED ENGLISH PRONUNCIATION TRAINING FOR YOUTH IN THE DEMOCARE COMMUNITY IN NORTH MERUYA - Irma Rahmawati; Wahyu Budi; Lutfi Alhazami; Ratu Amanah Amaranth Azalea; Gabriella Angelica (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This community service program aims to improve English pronunciation skills among teenagers in the North Meruya Youth Community in West Jakarta. The implementation method included training based on artificial intelligence (AI) applications such as Elsa Speak, which provides automatic feedback to improve articulation, intonation, and word emphasis. The activity was accompanied by mentoring through online groups and pre- and post-test evaluations using a scoring rubric on a scale of 1-5. Results showed that more than 90% of participants experienced a pronunciation score increase of at least 30%, with participant satisfaction levels reaching over 80%. The training successfully established independent study groups and increased participant confidence. These findings demonstrate the effectiveness of using AI technology in community-based English learning, with potential for replication in other regions.